Energy savings and cost-benefit analysis of using compression and absorption chillers for air conditioners in Iran - Shekarchian, M.; Moghavvemi, Mahmoud; Motasemi, F.; Mahlia, T.M.I. (Elsevier, 2013)
The electricity demand in Iran has increased steadily in recent years. This is mainly due to the rapid growth in the number of high-rise air-conditioned buildings and the rapid use of electrical appliances in residential and commercial sectors. This paper investigates the annual energy required for cooling per unit area and the total energy cost per unit area for each type of air conditioning systems in different climates in Iran. The paper also investigates the effects of changing the coefficient of performance (COP) of absorption chillers on cost saving. This study found that using absorption chillers for cooling will increase the amount of energy usage per unit area; however the energy cost per unit area will decrease. In addition this research indicates that for each 0.1 increment in COP of absorption chillers, there is at least 50 USD/m2 saved cost.